2014
DOI: 10.3109/10428194.2013.858812
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-related gene expression profile in childhood acute lymphoblastic leukemia: prognostic implications

Abstract: A cellular hypoxic condition is a key event in several human cancers, but knowledge about its role in childhood acute lymphoblastic leukemia (ALL) is very limited. In the present study, the gene expression profile of hypoxia-related genes (HIF1A, CA9, VEGF and SCL2A1) was evaluated in bone marrow samples of 113 pediatric patients. HIF1A mRNA up-regulation was significantly associated with higher 5-year event-free survival rates in patients with B-ALL as well as in the overall ALL population in both univariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Similarly, in CML, HIF-1alpha induction following short (5 h) hypoxia exposure delivered a survival signal to cells, whereas it promoted cell death within a longer period (22 h) ( 127 ). In the ALL model, 24 h-exposure to hypoxia conferred chemoresistance in contrast to longer exposure (48–72 h) ( 128 ). These data suggest that duration of hypoxia incubation may promote or inhibit leukemia progression and maintenance, thus explaining the oncogenic or tumor suppressor activity.…”
Section: Hypoxia-inducible Factors In Leukemiasmentioning
confidence: 99%
“…Similarly, in CML, HIF-1alpha induction following short (5 h) hypoxia exposure delivered a survival signal to cells, whereas it promoted cell death within a longer period (22 h) ( 127 ). In the ALL model, 24 h-exposure to hypoxia conferred chemoresistance in contrast to longer exposure (48–72 h) ( 128 ). These data suggest that duration of hypoxia incubation may promote or inhibit leukemia progression and maintenance, thus explaining the oncogenic or tumor suppressor activity.…”
Section: Hypoxia-inducible Factors In Leukemiasmentioning
confidence: 99%
“…In breast cancer, analysis of HRGs has been proposed as a tool for developing novel therapeutic strategies with molecular signatures 20 . The prognostic ability of HRGs is reported in many other malignancies, including gastric cancer, leukemia, and CRC 8,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, recent studies have suggested that single‐nucleotide polymorphisms in genes involved in placental function may be related to both stillbirths and ALL risk. Specifically, mutations in genes critical for normal placental function, such as the endothelial nitric oxide synthase, Klotho and hypoxic inducible factor‐1α genes, as well as polymorphisms of the vascular endothelial growth factor (VEGF) and tumour necrosis factor‐α genes, may result in abnormal prenatal development, fetal growth restriction, and late fetal death . Polymorphisms of the aforementioned genes may also play a pivotal role in the induction of neovascularisation in ALL by increasing the microvascular density in the bone marrow of children .…”
Section: Commentmentioning
confidence: 99%